2002
DOI: 10.1152/ajplung.00379.2001
|View full text |Cite
|
Sign up to set email alerts
|

Laminin α-chain expression and basement membrane formation by MLE-15 respiratory epithelial cells

Abstract: -Basement membranes have a critical role in alveolar structure and function. Alveolar type II cells make basement membrane constituents, including laminin, but relatively little is known about the production of basement membrane proteins by murine alveolar type II cells and a convenient system is not available to study basement membrane production by murine alveolar type II cells. To facilitate study of basement membrane production, with particular focus on laminin chains, we examined transformed murine distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The disruption of the integrity of the basement membrane caused by genetic defects in ␣ 3 and ␤ 1 integrin and kindlerin implicates these proteins in basement membrane assembly and maintenance and suggests that they are likely components of the same signaling pathway. TGF-␤ not only enhances kindlerin expression as shown in this report but also increases the abundance of integrins (61, 62) and extracellular matrix constituents such as fibronectin, collagen, and laminin (63)(64)(65)(66). Therefore, it is reasonable to postulate that organization of the newly synthesized extracellular matrix components by integrin and kindlerin complexes may be an important step in TGF-␤-stimulated cell motility.…”
Section: Discussionmentioning
confidence: 53%
“…The disruption of the integrity of the basement membrane caused by genetic defects in ␣ 3 and ␤ 1 integrin and kindlerin implicates these proteins in basement membrane assembly and maintenance and suggests that they are likely components of the same signaling pathway. TGF-␤ not only enhances kindlerin expression as shown in this report but also increases the abundance of integrins (61, 62) and extracellular matrix constituents such as fibronectin, collagen, and laminin (63)(64)(65)(66). Therefore, it is reasonable to postulate that organization of the newly synthesized extracellular matrix components by integrin and kindlerin complexes may be an important step in TGF-␤-stimulated cell motility.…”
Section: Discussionmentioning
confidence: 53%
“…The alveolar cells of the lung lie on a basement membrane composed of a complex of matrix proteins (Miner et al, 1997;Nguyen et al, 2002). In the intact lung, the production of laminin subunits is developmentally regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work by LEE et al [32] demonstrated that IL-13 induces lung fibrosis in mice by selective activation of transforming growth factor-b (TGF-b). TGF-b induces expression of laminin a1 chains in rat mesangial cells [33] and laminin c1 chains in mouse distal respiratory epithelial cells [34]. The ability of laminin, via a laminin/nidogen binding site, to form a lattice-type assembly with collagen in the lung matrix may lead to airway wall thickening.…”
Section: Discussionmentioning
confidence: 99%